Synthesis of Fin-Shaped Zeolite Crystals
By forming fins on the surface of zeolite crystals, the problem of difficult preparation of zeolites with sizes less than 100nm in the prior art is solved, the catalyst performance and life are improved, and an efficient catalyst platform is realized, providing new application methods for the petrochemical industry. .
Patent Information
- Application Number
- CN202180026621.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-12
- Filing Date
- 2021-02-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-02-09
AI Technical Summary
The prior art is difficult to prepare zeolite crystals with a size less than 100 nm, and the synthetic yield of nano-sized zeolites is low, expensive organic matter is required, and difficult to separate and prepare as catalysts, which limits the large-scale production and application of zeolites.
Using the post-synthesis route of fin-shaped zeolite crystals, fins are formed on the surface of zeolite crystals by seeding seed method, and the density and size of fins are optimized using secondary growth solutions and conditions, and it is generalized to a variety of zeolite skeleton types, including ZSM-5 , ZSM-11 and ferrosteine zeolite form microporous materials with reduced diffusion limitations.
It improves the performance and life of the catalyst, reduces the catalyst deactivation rate, changes product selectivity, provides an efficient catalyst platform suitable for the petrochemical industry, avoiding the use of expensive organic matter and pore blockage problems.
Smart Images

Figure CN115397777B_ABST
Abstract
Description
Background Art
[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 975,254, filed on February 12, 2020, entitled “Synthesis of Finned Zeolite Crystals,” the entire contents of which are incorporated herein by reference.
[0002] This invention was made with government support under Grant DE-SC0014468 from the Department of Energy, Basic Energy Sciences. The government has certain rights in this invention.
[0003] The present disclosure relates to the synthesis of finned zeolite crystals.
[0004] It is well established that zeolite crystal size affects the mass transfer characteristics of the zeolite in adsorption, separation, ion exchange, and catalysis (to name a few). In the case of zeolite catalysis, it is well established that smaller crystal size increases catalyst life (depending on the reaction conditions) and also affects product selectivity. Smaller size results in a reduction in the average residence time of reactants and products within the zeolite pores. This reduction in internal diffusion path length, for example, reduces the rate of coking (i.e., carbon deposits that block the pores), thereby extending catalyst life and may change the number of secondary reactions that occur in the pores, which affects selectivity.
[0005] Previously, researchers reported that relatively few of the approximately 250 known zeolites could be prepared with sizes less than 100 nm. However, the synthesis of nano-sized zeolites is usually in low yield, and they usually require the use of expensive organics. All of these factors pose a problem for the large-scale production of zeolites. In addition, only a small number of these structures have achieved only 2-dimensional materials (size 2-10 nm), and are difficult to separate and prepare as catalyst formulations. Many conventional syntheses of zeolites ZSM-5 (MFI) and ZSM-11 (MEL) with considerable aluminum content (i.e., Si / Al < 40) rarely produce crystals with sizes less than 100 nm.
[0006] Methods reported to reduce diffusion limitations include the preparation of nanosized (10-100 nm in size) zeolites and 2-dimensional zeolites (2-10 nm in size). Achieving such small sizes is generally not trivial and involves a multi-step process that often involves the use of organic structure directing agents, many of which are not commercially available. Summary of the invention
[0007] The present application generally relates to a post-synthetic route for preparing a new class of microporous materials (referred to as "finned" zeolite crystals) with reduced diffusion limitations. Inspired by traditional fins that enhance interfacial heat transfer, finned zeolite crystals include seeds (characteristic size β) and epitaxially grown protrusions (characteristic size α, where α << β). The growth of the protrusions is accomplished by a seeding method, in which the zeolite crystals are placed in a secondary growth solution, thereby forming a rough interface on the surface of the seed due to a large number of fins. The growth solution and conditions of the secondary synthesis are designed in such a way that the homogeneous nucleation of new crystals is minimized and the fins are preferentially grown on the seeds. The conditions of the secondary growth can be adjusted to change the density (or coverage) and size of the fins. This method can be extended to a wide range of zeolite framework types. The synthesis of finned zeolites has been demonstrated on three different crystal structures: ZSM-5 (MFI), ZSM-11 (MEL) and ferrierite (FER). Both the MEL and MFI frameworks include medium-sized channels that intersect in 3 dimensions, whereas the FER framework includes small- and medium-sized channels that intersect in 2 dimensions.
[0008] The methods disclosed herein rely on post-synthetic modification of existing (seed) crystals. Fins can be generated by a one-pot method; however, the exact set of synthesis conditions is unpredictable and therefore less universal for a large class of crystal structures. The seed growth method is a more reproducible (and predictable) method for producing fin-shaped materials. One of the difficulties in preparing finned zeolites is to determine the growth mixture that promotes nucleation and protrusion growth on the surface of the seed crystal. Systematic experiments have determined the optimal conditions for the formation of finned zeolites. The conditions that can be manipulated to adjust the finned zeolites include (but are not limited to) temperature, introduction of organic matter, synthesis time, supersaturation (ie, silica and / or alumina concentration), sources of silica and alumina, and alkalinity. For example, synthesis at high temperature can promote homogeneous nucleation of crystals separated from the seed crystals, resulting in a bimodal distribution of crystal sizes (or crystal aggregates). In contrast, low-temperature synthesis may not be sufficient to nucleate into fins on the surface of zeolite seed crystals.
[0009] The present synthesis method produces finned zeolite crystals with bulk performance similar to that of crystals with a smaller size of about α (the average size of the fin-like protrusions) as shown by catalytic testing. This suggests that the introduction of fins leads to improved catalyst performance and may also extend to other applications such as adsorption, separation or ion exchange, where internal diffusion affects the overall performance of the zeolite.
[0010] Finned zeolites, despite having a larger net size than the seed crystals, behave as catalysts with sizes smaller than the seed crystals. The methanol to hydrocarbons (MTH) reaction showed a nearly 3-fold reduction in catalyst deactivation relative to conventional zeolite crystals. A shift in the dominant hydrocarbon pool mechanism was also observed for finned zeolites, resulting in product selectivities similar to smaller crystals. Overall, the results show that this modification approach improves catalyst performance, thereby providing an efficient and versatile platform for the synthesis of optimal zeolite catalysts with reduced diffusion limitations for a variety of applications in the (petro)chemical industry. This approach also allows the modification of existing commercial catalysts via a simple secondary growth approach.
[0011] The finned zeolites described herein have distinctly unique properties compared to similarly sized crystals without fins. The secondary growth method used to prepare the finned zeolites is applicable to a wide range of zeolite crystal structures. There is no known prior art that employs seeded (or secondary) growth to obtain finned materials. Most syntheses in the published literature / patents report crystals with rough features due to the presence of aggregates or fused crystals. In these materials, the improved performance reported in these studies is due to the bimodal distribution of small and large crystals and the mesoporosity introduced by their aggregated morphology. In the present technology, the fins are epitaxially grown on the seed surface (meaning that the fins and the seed exhibit the same crystallographic registry); therefore, the enhanced performance is not due to mesoporosity. In addition, the present technology is superior to mixtures of small and large crystals for several reasons: (1) small crystals are challenging to prepare by conventional methods; (2) contact between small and large crystals can lead to pore blockage, which negatively affects internal mass transfer; (3) the synthesis of mixtures of small and large crystals can be difficult to control in zeolite synthesis scale-up; and (4) small crystals can be lost during some processes such as filtration and catalyst manufacturing (e.g., spray drying). In the present technology, the pore network between the fins and the seeds is continuous, thus avoiding pore blockage. It should be noted that the method used in the present technology also circumvents the need for expensive organics, thus making the present method more economical than existing technologies that rely on exogenous organics to produce hierarchical (or 2D) zeolite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Shown are (A) an idealized schematic diagram of a finned zeolite with fin size α, internal width β, and gap (or spacing) γ between adjacent fins, (B) scanning electron micrograph of ZSM-11 with finned surface prepared from MEL-fin growth solution (Table 1), and (C) continuous reaction time methanol conversion for H-ZSM-11 catalysts with different crystal sizes.
[0013] Figure 2 Shown are (A) a scanning electron microscope (SEM) image of a ZSM-11 crystal (seed), (B) an SEM image of ZSM-11 after secondary growth to produce fins, (C) an idealized schematic of a finned zeolite in which the fins have the same crystallographic orientation as the seeds, (D) an SEM image of a ZSM-5 crystal (seed), (E) an SEM image of ZSM-5 after secondary growth to produce fins, and (F) a schematic of a finned zeolite including continuous channels running through the seeds (characteristic dimension β) and the fins (characteristic dimension α).
[0014] Figure 3 Shown are (A) a plot of the continuous reaction time below complete methanol conversion during the methanol to hydrocarbons reaction over an H-ZSM-11 catalyst (seed / fin), (B) a plot of the continuous reaction time below complete methanol conversion over an H-ZSM-5 catalyst (seed / fin), (C) the selectivity of hydrocarbon products for seeded and finned H-ZSM-11 samples, (D) the selectivity of hydrocarbon products for seeded and finned H-ZSM-5 samples, (E) the ratio of ethylene to 2-methylbutane and 2-methyl-2-butene products (2MBu) as a function of continuous reaction time (TOS) for four groups of samples, (F) an SEM image of a commercial sample, (G) an SEM image of a corresponding finned commercial sample prepared by secondary growth, and (H) the methanol conversion of pristine material and finned commercial H-ZSM-5 under the same reaction conditions.
[0015] Figure 4 The H-ZSM-5 samples (seed and fin) were shown to be fully crystalline as confirmed by powder X-ray diffraction (XRD).
[0016] Figure 5 Show from Figure 1 All H-ZSM-11 samples of C (to which seeds for preparing fin-shaped samples were added) were fully crystalline according to their powder X-ray diffraction (XRD) patterns.
[0017] Figure 6 N2 adsorption / desorption isotherms of ZSM-5 seeds and fin samples are shown.
[0018] Figure 7 N2 adsorption / desorption isotherms of ZSM-11 seeds and fin samples are shown.
[0019] Figure 8 Scanning electron micrograph showing ferrierite crystals used as seeds (denoted FER-seeds).
[0020] Fig. 9Scanning electron micrographs showing fin-shaped ferrierite crystals prepared by seed secondary growth at different synthesis temperatures: (A) FER-Fin 1 at T = 120°C, (B) FER-Fin 2 at T = 130°C, and (C) FER-Fin 3 at T = 140°C.
[0021] Fig.10 show Fig. 9 Powder X-ray diffraction (XRD) patterns of the seed and finned ferrierite samples shown.
[0022] Fig.11 Shown are N2 adsorption / desorption isotherms for seed and finned ferrierite crystals prepared by secondary growth. DETAILED DESCRIPTION
[0023] The present application relates to a method for synthesizing finned zeolite crystals.
[0024] The present synthesis method solves the limitation in conventional zeolite synthesis, uses the seed growth (or secondary growth) scheme with the potential of improving the performance of given zeolite to optimize the catalyst performance. Such method can be used, for example, to improve the performance of zeolite catalysts for industrial application in the petroleum and petrochemical industries. The preferred embodiment described herein includes the synthesis of ZSM-5 (MFI), which is one of the most widely used catalysts as heterogeneous catalysts in the petroleum industry. Another preferred embodiment relates to the synthesis of ZSM-11 (MEL), which has attracted much attention in the industry due to its topological structure similar to MFI or ferrierite (FER).
[0025] Preferred embodiments described herein relate to methods for preparing finned zeolites, wherein the size of the protrusions (or fins) is α <50 nm. The performance of finned zeolite catalysts in the MTH reaction indicates that they act similarly to crystals of size α rather than the overall size of the particles (which can be about 400 nm). Therefore, the present method avoids the challenges of directly synthesizing nano-sized zeolites and allows the performance of larger crystals (including existing commercial zeolites) to be improved by secondary growth methods. This method is versatile in design, allowing fins of different sizes and densities (the number of fins per unit surface area of the seed) to be grown on zeolite seeds with a wide range of crystal structures (i.e., a variety of zeolite framework types). The results of the study showed that the fins improved the internal mass transfer characteristics, which opened up new avenues for their use in a variety of applications, including (but not limited to) catalysis, separation, adsorption, and ion exchange.
[0026] This article describes the successful synthesis of finned zeolites for 2- and 3-dimensional structures, but the approach can be generalized to a broad class of zeolitic materials.
[0027] The preferred embodiments described herein relate to a method for preparing fin-shaped zeolite crystals, the method comprising the step of preparing a secondary growth solution for epitaxially growing fin-shaped protrusions from zeolite seed crystals. In a preferred embodiment, the secondary growth solution comprises one or more framework source precursors, one or more structure directing agents, and a hydroxide source. In a preferred embodiment of the method, an additional step is to add zeolite seeds in an amount of about 5% by weight to about 30% by weight of the secondary growth solution to produce a seed growth solution. In a preferred embodiment of the method, an additional step is to heat the seed growth solution to a temperature of about 100°C to about 170°C for about 6 hours to about 48 hours. In a preferred embodiment of the method, an additional step includes quenching the seed growth solution to room temperature to produce a final growth solution and separating the fin-shaped zeolite crystals from the final growth solution.
[0028] In a further preferred embodiment of the method, the one or more framework precursors comprise one or both of a silica source and an alumina source. In other preferred embodiments of the method, the one or more framework precursors include sodium silicate, tetraethyl orthosilicate, colloidal silicate, fumed silica, SiO2, aluminum sulfate, aluminum hydroxide, Al2O3, or a combination thereof. In a further preferred embodiment, the one or more structure directing agents are inorganic structure directing agents, organic structure directing agents, or a combination thereof. The first structure directing agent may be the same as or different from the second structure directing agent. In a further preferred embodiment, the structure directing agent (SDA) is selected from pyrrolidine, tetrapropylammonium hydroxide, 1,8-octanediamine, cyclohexylamine, and tetrabutylammonium hydroxide. In a further preferred embodiment, the hydroxide source is Na2O or K2O. In other preferred embodiments of the method, the secondary growth solution has a molar composition ratio of one framework source precursor to another framework source precursor of about 40:1 to about 120:1, which may be about 40:1 to about 120:1 SiO2 / Al2O3. In other preferred embodiments of the method, the secondary growth solution has a molar composition ratio of a framework source precursor to a structure directing agent of about 2:1 to about 15:1, and the framework source precursor may be SiO2. In other preferred embodiments of the method, the secondary growth solution has a molar composition ratio of a framework source precursor to a hydroxide source of about 8:1 to about 65:1, and the framework source precursor may be SiO2. Other preferred embodiments include finned zeolite crystals prepared by the method. In preferred embodiments, the finned zeolite crystals are MEL type, MFI type or FER type.
[0029] Further preferred embodiments described herein include finned zeolite crystals, which include a zeolite seed portion and a plurality of epitaxially grown protrusions or fins extending from the outer surface of the zeolite seed portion. The zeolite seed portion includes a single crystallographic positioning and a pore network. The epitaxially grown protrusions include a single crystallographic positioning identical to the zeolite seed portion due to epitaxial growth. The epitaxially grown protrusions also include a pore network continuous with the pore network of the seed portion due to epitaxial growth. In other preferred embodiments of finned zeolite crystals, the zeolite seed portion has a characteristic size β, the epitaxially grown protrusions have a characteristic size α, and β is greater than α. In further preferred embodiments, α is less than about 50nm. In other preferred embodiments, the average spacing δ (or gap) between adjacent fins is about 20nm to about 100nm. In other preferred embodiments, the finned zeolite crystals are MEL type, MFI type or FER type.
[0030] The growth solutions selected for MFI, MEL, and FER take advantage of the fact that zeolites tend to grow through non-classical pathways that involve the attachment of amorphous precursors or substances more complex than the framework-derived precursor monomers. This enables the fins to grow in 3 dimensions on the surface of the seed crystal. The scheme for generating finned zeolites is strategically selected by adjusting the supersaturation to a high enough level to avoid growth by monomer addition, which can lead to smooth overgrowth (or two-dimensional growth) of the seed crystal. At the same time, there is an upper limit of supersaturation, which, when exceeded, leads to homogeneous nucleation of new crystals in the growth solution, resulting in aggregates of both small and large crystallites. Given that many zeolites are prepared from solutions of similar composition and there are various precursors, it is expected that this approach can be extended to a wide class of zeolite framework types.
[0031] Example 1
[0032] This example investigates alternative approaches to reduce internal diffusion limitations in zeolite catalysts, focusing on two common 3-dimensional medium-pore zeolites: ZSM-11 (MEL type) and ZSM-5 (MFI type).
[0033] All reagents were used directly without further purification. The following reagents were used for zeolite synthesis: tetraethyl orthosilicate (TEOS, 98%, Sigma Aldrich), LudoxAS-30, NaOH, KOH, 1,8-octanediamine (DAO, 98%, SigmaAldrich), Al2(SO4)3, sodium aluminate (technical grade, AlfaAesar), sodium hydroxide (>98%, Sigma-A1drich), tetrabutylammonium hydroxide (TBAOH, 40%, Sigma-Aldrich), and tetrapropylammonium hydroxide (TPAOH, 40%, AlfaAesar). Deionized (DI) water used in all experiments was purified using an Aqua Solutions Type I RODI filter system (18.2 MΩ). The 1.0 M ammonium nitrate solution used for ion exchange was made from ammonium nitrate salt (NH4NO3, ACS reagent, ≥98%, Sigma-Aldrich) and DI water. For the reaction test, the zeolite catalyst was pelletized and sieved (40-60 mesh), and 36.9 mg of the sieved catalyst particles were diluted with 113.1 mg of silica gel (Davisol 636 grade, 35-60 mesh size, Sigma-Aldrich).
[0034] For the synthesis of conventional ZSM-11 zeolite, for comparison purposes, a non-seed method (or one-pot method) for synthesizing finned zeolites was used, with TBAOH used as an organic structure directing agent (OSDA). In a typical synthesis, 0.220 g of sodium aluminate was added to a mixture of 0.786 g of NaOH solution (43 mg / g solution) and 5.36 g of DI H2O. 5.925 g of TBAOH was added to the solution, followed by the addition of a silica source, TEOS (9.707 g). The resulting mixture was stirred at room temperature for 2 hours in a sealed bottle to hydrolyze TEOS. The resulting solution was placed in a 60 mL Teflon-lined sealed metal autoclave (Parr Instruments) and heated in a Thermo Fisher Precision oven at a temperature of T = 170 ° C and autogenous pressure. After 3 days, the autoclave was removed from the oven and quenched to room temperature in water. The molar composition of the synthesis mixture listed in Table 1 below was varied to synthesize conventional and one-pot finned ZSM-11 / ZSM-5 samples. The synthesis procedure for the ZSM-5 samples was identical to that for ZSM-11, except that TPAOH was used as the OSDA. The crystalline product was removed from the mother liquor by three centrifugation cycles (10 minutes each) and washing with DI water using a Beckman Coulter Avanti JE centrifuge at 5°C and 13000rpm. The samples used for catalysis were calcined at 550°C for 5 hours in a Thermo Fisher Lindberg Blue furnace under a constant flow of dry air (Matheson Tri-Gas) with a temperature increase / cooling rate of 1°C / min. These samples were converted to the acid form [Bronstedt acid], wherein the calcined zeolite was mixed with 1.0 M ammonium nitrate solution to obtain a 2 wt% suspension. The mixture was heated to 80°C for 2 hours to generate NH4 + Exchange Na + This process was carried out three times with washing between each ion exchange cycle. The final NH4-zeolite sample was washed three times with DI water and then calcined again using the same procedure as above to produce H-type zeolite.
[0035] Table 1. Synthesis conditions of conventional and finned zeolite ZSM-11 samples synthesized by one-pot process
[0036]
[0037] The ZSM-11 sample used as seed was prepared using a molar composition of 10DAO: 10K2O: 100SiO2: 1Al2O3: 4000H2O. In a typical synthesis, 0.185 g of aluminum sulfate, Al2(SO4)3, was added to a mixture of 0.61 g of potassium hydroxide solution (KOH, 50 wt%) and 15.35 g of deionized (DI) H2O. According to the method outlined above, 0.40 g of 1,8-diaminooctane (DAO) was added to the solution, followed by 5.45 g of colloidal silica (LUDOXAS-30) and 2 wt% of calcined ZSM-11 (YF Shen, TTL, R. Li, JD Rimer, 'Optimized synthesis of ZSM-11 catalysts using 1,8-diaminooctane as a structure-directing agent". ChemPhysChem 19, 529-537, 2018, incorporated herein by reference). The resulting mixture was stirred at room temperature for 24 hours. The sol-gel was then placed in 60 mL The seeds were separated by several centrifugation / washing cycles and the resulting seeds were immediately stored in DI water without allowing time for the solids to dry. A seed growth solution was prepared using a molar composition of 27.3 DAO: 11.9 K2O: 90 SiO2: 0.5 Al2O3; 3588 H2O. The solution was prepared by adding an appropriate amount of Al2(SO4)3 to a solution containing KOH and DI water, followed by the addition of DAO and LUDOXAS-30. The mixture was stirred for 3 hours. Stir at room temperature for 24 hours, then add 10 wt% ZSM-11 seeds (relative to the total amount of growth solution). The suspension is heated at 120°C for 2 days. The solids are extracted from the mother liquor using multiple centrifugation / washing cycles. The ZSM-5 sample used as seed was prepared using a molar composition of 15TPAOH:4Na2O:100SiO2;1.67Al2O3:2500H2O;400EtOH. In a typical synthesis, 0.094 g of sodium aluminate was added to 1.022 g of sodium hydroxide solution (NaOH, 46 mg / g solution) and 12.17 g of DI H2O mixture. To this solution, 6.41 g of tetraethyl orthosilicate (TEOS) was added, followed by OSDA, tetrapropylammonium hydroxide (TPAOH, 2.30 g). The resulting mixture was stirred at room temperature for 2 hours, and then the sol-gel was heated in an oven at T = 170 ° C and autogenous pressure for 2 days. The separated seeds were immediately placed in DI water for storage. A solution for seed growth was prepared using a molar composition of 10 TPAOH: 0.5 Na2O: 31.5 SiO2: 0.5 Al2O3: 1660 H2O.The solution was prepared similarly to the seeding protocol, with the addition of 5 wt% ZSM-5 seeds (relative to the total amount of growth solution) after aging of the secondary growth solution. The mixture was heated at 100°C for 24 hours and the solid was extracted as a white powder. The selection procedure used an additional thermal annealing step, in which the centrifuged gel was directly transferred to a solution of composition 10TEOS:14TPAOH:9500H2O, which was heated at 170°C for 7 days. The solution was then removed from the oven and the solid was dried in air after multiple centrifugation and washing cycles. The molar composition of the synthesis mixture listed in Table 2 below was varied to synthesize seeded and seed-assisted finned ZSM-11 / ZSM-5 samples.
[0038] Table 2. Synthesis conditions of seeds and growth solutions for fin-shaped ZSM-11 and ZSM-5 samples prepared by seeded synthesis
[0039]
[0040] a. "M" = alkali ion; respectively, Na2O for ZSM-5 and K2O for ZSM-11;
[0041] b. TPAOH is used for ZSM-5 and DAO is used for ZSM-11;
[0042] c. Using 2 wt% ZSM-11 calcined seeds (relative to the SiO2 content in the synthesis mixture).
[0043] The H-type zeolite was characterized by powder X-ray diffraction (XRD) using Cu Kα radiation using a Rigaku SmartLab diffractometer to verify the crystal structure. The powder XRD pattern was compared with the simulated patterns of each framework type provided by the International Zeolite Association Structure Database. The average crystal size was determined from scanning electron microscope (SEM) images taken by a FEI 235 dual beam (focused ion beam) instrument. Elemental analysis of the H-type zeolite was performed by inductively coupled plasma (ICP) analysis using a JEOL SM-31010 / METEK EDAX system at 15 kV and 15 mm working distance to confirm the completion of ion exchange and quantify the Si / Al molar ratio. To confirm the uniform distribution of Al in the crystal, surface elemental analysis was performed using a PHI 5800ESCA (Physical Electronics) system with a standard achromatic Al Kα X-ray source (1486.6 eV) and a concentric hemispherical analyzer operating at 300 W (15 kV and 20 mA). Since zeolite is an insulating material, a device neutralizer component was used to prevent charging effects. All data were collected at a 45° takeoff angle, and the collected spectra were analyzed using the MultiPak program. Using a Micromeritics ASAP 2020 instrument, textural analysis of the H-type sample was performed using N2 adsorption to obtain the BET surface area, and the micropore volume was determined by the t-plot method.
[0044] The synthesis of ZSM-11 using conventional protocols produces crystals with relatively smooth outer surfaces. Figure 2 A shows a scanning electron micrograph of ZSM-11 with a smooth surface prepared by the conventional protocol. An alternative one-pot synthesis of ZSM-11 produces crystals with highly rough outer surfaces. Figure 1 B shows a scanning electron micrograph of ZSM-11 with a fin-like surface prepared from a non-seeded growth solution with a molar composition of 10DAO:10K2O:100SiO2:1Al2O3:4000H2O. Figure 2B shows a scanning electron micrograph of a representative fin-shaped ZSM-11 crystal prepared by seeded growth. Transmission electron microscopy (TEM) shows that these are single crystals with the same register between the center of the particle and its outer rough features, where the rough features are aligned in the same direction and have an average size of 30nm. Elemental analysis shows that the composition of the seeds and fins is roughly similar, with no evidence of aluminum zoning. In addition, texture analysis shows no evidence of mesoporosity in the ZSM-11 sample.
[0045] Previous studies have reported crude crystals of ZSM-11 and ZSM-5; however, these structures are significantly different from those reported. Notably, the crude crystals in the literature are typically aggregates of small crystallites arranged in random orientation on the outer surface of larger particles. This structure produces misoriented regions that block pores at the interface boundaries between adjacent particles and also produces interparticle mesopores. Previous studies have demonstrated that these aggregated structures enhance catalytic performance relative to traditional analogs, which is generally attributed to the introduction of interstitial mesopores. As shown herein, the synthesis of fin-shaped ZSM-11 produces improved catalytic performance due to a different mechanism: enhanced mass transfer within smaller areas (i.e., fins) that decorate the outer surface. Using the methanol to hydrocarbons (MTH) reaction, trends in catalyst life and selectivity have previously been reported to vary with H-ZSM-11 crystal size (150, 300, and 750 nm). The characteristics of these three catalysts (Si / Al≈20) were compared with a fin-shaped H-ZSM-11 sample with an overall size of approximately 400 nm and an average fin size of approximately 30 nm.
[0046] Methanol conversion over H-type catalyst was carried out in a 1 / 4 inch stainless steel tube mounted in a Thermo Scientific Lindberg Blue M furnace. The catalyst bed was supported between two quartz plugs, and a K-type thermocouple (Omega Engineering) was inserted into the stainless steel tube to measure the temperature of the catalyst bed. Prior to the reaction, the reactor was heated in a dry air stream (6 cm 3 / min O2,24cm 3 The catalyst bed was pretreated in situ at 550°C for 3 h under N2 ( / min). After the pretreatment, the catalyst bed was cooled to the reaction temperature, i.e., 350°C. Methanol was introduced into the heated Ar inert gas stream (30 cm / min) at 7 μL / min via a syringe pump (Harvard Apparatus). 3 / min), which results in a weight hourly space velocity (WHSV) of the reactant stream of 9h -1 In order to kinetically compare the deactivation rates of the catalysts, the reactions were also carried out at a low methanol conversion (X), defined as
[0047]
[0048] Among them C 出 is the carbon-based molar concentration of methanol and dimethyl ether (DME) in the effluent, C 入 is the concentration of methanol in the influent. The selectivity of hydrocarbon product i (S i ) is defined as
[0049]
[0050] Among them C i is the carbon-based molar concentration of hydrocarbon i in the effluent, C t,出 is the total carbon-based molar concentration of hydrocarbons in the effluent.
[0051] Figure 1 C shows that at 350℃ and WHSV=9h -1 Continuous reaction time methanol conversion of H-ZSM-11 catalyst during the MTH reaction. The performance of fin-shaped H-ZSM-11 with an overall size of 400nm (fins ≈ 30-50nm) is compared to smooth H-ZSM-11 crystals with sizes of 750nm (diamonds), 300m (squares), and 150nm (circles). The dashed lines are insets to guide the view. Interestingly, when the comparison is made on the basis of overall particle size, the fin-shaped sample deviates from the trend of increasing lifetime as crystal size decreases; however, the trend is consistent if the fin-shaped sample behaves as if it were a crystal of much smaller size.
[0052] Since the effects of synthesis parameters on zeolite crystallization are largely unknown, the preparation of fin-shaped crystals by one-pot synthesis is arbitrary and difficult to predict. For this reason, secondary (or seed) growth provides a more controllable method to produce fins on the outer surface of the seed crystal. The secondary growth method has been demonstrated for both ZSM-11 and ZSM-5.
[0053] Figure 2 A and Figure 2 D shows scanning electron microscope (SEM) images of ZSM-11 and ZSM-5 crystals (seeds) prepared by conventional protocols, respectively. These images of ZSM-11 and ZSM-5 seeds show external crystal surfaces without rough features. Figure 2 B and Figure 2E shows SEM images of ZSM-11 and ZSM-5 after secondary growth, respectively, confirming the presence of fins. The synthesized zeolites were also characterized by powder X-ray diffraction (XRD) to verify the crystal structure with relative simulated maps. The samples before and after seed growth were compared by texture analysis, which showed a slight increase in total surface area (about 8%) with secondary growth, while the micropore volume did not change significantly. Elemental analysis also confirmed that the Si / Al molar ratio of the samples before and after seed growth was almost the same.
[0054] The fin generation scheme is strategically chosen by adjusting the supersaturation to a sufficiently high level to avoid the growth of core-shell particles (i.e., delamination overgrowth of seeds leading to smooth interfaces). However, there is an upper supersaturation limit that, when exceeded, leads to homogeneous nucleation of new crystals in the growth solution, resulting in aggregates of small and large crystallites. Figure 2 C shows an idealized schematic of a finned zeolite, where the fins have the same crystallographic orientation as the seeds. Figure 2 F shows an idealized schematic diagram of a finned zeolite comprising continuous channels through the seed (characteristic dimension β) and the fins (characteristic dimension α), where the channels connect the entire interior and exterior having the same orientation.
[0055] The performance of the acid exchanged (H-form) seed and fin samples was also evaluated at less than full methanol conversion (60-90%) in the MTH reaction to compare the relative rates of catalyst deactivation and product selectivity. The physicochemical properties of all catalysts were evaluated to confirm their similarity in terms of acid site density, ensuring that each reaction was run at a fixed weight hourly space velocity (WHSV). Figure 3 A and Figure 3 B shows that at 350℃ and WHSV=20h -1 Figure 3. Continuous reaction time plots for less than full methanol conversion during the MTH reaction for H-ZSM-11 and H-ZSM-5 catalysts, for seeded (squares) and finned (diamonds) samples. The insets show schematic diagrams of the MEL and MFI framework topologies, respectively. Continuous reaction time (TOS) analysis shows almost identical starting conversions, indicating similar catalyst activities. This suggests that the reaction in the finned samples is not limited to the external protrusions (fins), but also occurs inside the catalyst. This is qualitatively consistent with TEM and texture analysis, showing epitaxial growth of the fins without obvious pore blocking at the fin-seed boundaries. In both sets of materials, a reduction in catalyst deactivation of about 3 times was observed; therefore, the presence of the fins significantly extends the catalyst lifetime. Figure 3 C and Figure 3D shows the hydrocarbon product selectivity of the seeded and finned H-ZSM-11 and H-ZSM-5 samples, respectively, evaluated at 60-90% methanol conversion. Comparison of product selectivities shows a subtle shift, where the finned zeolite appears to act like smaller crystals, promoting the olefin-based cycle of the MTH hydrocarbon pool (HCP) mechanism. Previous studies have shown that the preferred cycle (from aromatics to olefins) gradually shifts as crystal size decreases. This is evident when comparing the conventional descriptor ethylene / 2MBu, a marker product ratio from the aromatic-based cycle (ethylene) and the olefin-based cycle (2MBu = 2-methylbutane and 2-methyl-2-butene). Figure 3 E shows the ratio of ethylene to 2-methylbutane and 2-methyl-2-butene products (2MBu) for the four groups of samples. A significant decrease in the ethylene / 2MBu ratio is observed for the finned catalyst over the entire methanol conversion range, which is consistent with the expected trend for smaller particles.
[0056] One advantage of the fin synthesis method is that it is theoretically applicable to a wide range of framework types. In addition, this method can be used to upgrade commercial catalysts by adding a secondary growth step to produce fins with enhanced mass transfer characteristics. Seed growth experiments were performed using a commercial ZSM-5 sample (Zeolyst International, CBV5524G, Si / Al=25). SEM images of the original H-ZSM-5 showed an uneven particle size distribution with a size range of 150nm to 350nm ( Figure 3 F) Secondary growth of these particles successfully produced fin-shaped H-ZSM-5 without changing the density of Brønsted acidic sites. Figure 3 G shows an SEM image of a fin-shaped H-ZSM-5 sample prepared by secondary growth of a commercial sample. The MTH reaction at less than full methanol conversion on the commercial seed and fin-shaped catalysts showed that the latter exhibited a reduction in deactivation rate, similar to the results for the synthetic H-ZSM-5 sample ( Figure 3 H).
[0057] Example 2
[0058] Ferrierite (FER type) is a 2-dimensional zeolite consisting of 10-membered ring (MR) channels (0.43 nm x 0.55 nm) parallel to the
[001] direction and intersecting with 8MR channels (0.35 nm x 0.48 nm) in the
[010] direction. The ferrierite cages located at the intersection of the 6MR channels and the 8MR channels are generally associated with their catalytic action. In the present application, a synthetic method for producing fin-shaped ferrierite crystals is described. The application of this method to ferrierite provides evidence that the method is not limited to 3-dimensional zeolite frameworks (MFI and MEL types) but can be extended to zeolite frameworks with lower pore sizes.
[0059] Firstly, ferrierite seeds (FER-seeds) were synthesized by conventional procedures. Figure 8 Electron micrograph of ferrierite crystals used as seeds (FER-seeds) prepared by conventional protocols is shown. These seeds have a relatively smooth surface, ie without distinct protrusions.
[0060] Finned ferrierite materials with different protrusion (fin) size ranges from 40nm to 80nm are produced by controlling appropriate synthesis conditions. These finned materials were prepared under different synthesis conditions, including the organic structure directing agent cyclohexylamine (CHA). Ferrierite seeds were synthesized by a hydrothermal method using a molar composition of 4.8NaOH:1.0 Al2O3:20SiO2:5.0 CHA:1.2KOH:750H2O. In a typical synthesis, 7.22g of silica source colloidal silica was added to a mixture of sodium aluminate solution (15.1wt% Na2O, 16.8wt% Al2O3) and 15.49g DI H2O. To the solution were added 0.05g NaOH solution (10wt%) and 0.24g KOH (50wt% solution), followed by CHA (0.90g). The resulting mixture was stirred at room temperature to obtain a homogeneous solution. The gel solution was placed in a 60 mL Teflon-lined sealed metal autoclave (Parr Instruments) and heated in a Thermo Fisher Precision oven at 165°C and autogenous pressure. The autoclave was removed from the oven after 2 days of synthesis and quenched to room temperature. For the secondary growth of ferrierite seeds, a solution with a molar composition of 6.2Na2O:0.71Al2O3:20SiO2:14Pyr:800H2O was prepared. The solution was prepared by mixing approximately the amount of Al2(SO4)3·18H2O and water, followed by the addition of silica and hydroxide. Finally, the organic structure directing agent pyrrolidine (Pyr) was added to the solution. The resulting mixture was stirred at room temperature for 3 hours. Then, 20 wt% ferrierite (wet synthetic seeds) was added to the solution for secondary growth. The suspension was placed in a Teflon-lined autoclave and heated at different temperatures (120°C to 140°C) for 24 hours and then quenched to room temperature in water. The solution was then removed from the oven and the solids were dried in air after multiple centrifugation / washing cycles.
[0061] Fig. 9 Electron micrographs showing fin-shaped ferrierite crystals prepared by seeded secondary growth at different synthesis temperatures: (A) FER-Fin 1 at T = 120°C, (B) FER-Fin 1 at T = 130°C, and (C) FER-Fin 3 at T = 140°C. Fig.10Powder X-ray diffraction (XRD) patterns of seeded and finned ferrierite samples are shown. These powder XRD patterns confirm that the samples are fully crystalline with no significant impurities before and after seed growth. Fig.11 Liquid N2 adsorption / desorption isotherms are shown for seed and fin ferrierite crystals prepared by secondary growth. This textural analysis shows that the total surface area increases slightly with secondary growth without sacrificing micropore volume.
Claims
1. A method for preparing fin-shaped zeolite crystals, comprising: preparing a secondary growth solution for epitaxially growing fin-shaped protrusions from zeolite seed crystals, wherein the secondary growth solution comprises one or more framework source precursors, one or more structure directing agents, a hydroxide source, and water, wherein the one or more framework source precursors include one or both of a silica source and an alumina source; adding zeolite seeds in an amount of 5 wt % to 30 wt % of the secondary growth solution to produce a seed growth solution, the seed growth solution being used for post-synthesis modification of existing zeolite seeds; heating the seed growth solution to a temperature of 100° C. to 170° C. for 6 to 48 hours to produce epitaxially grown fins on existing zeolite seeds in the seed growth solution; quenching the seed growth solution to room temperature to produce a final growth solution; as well as Finned zeolite crystals are separated from the final growth solution, wherein the finned zeolite crystals include a zeolite seed portion and a plurality of epitaxially grown fins extending from an outer surface of the zeolite seed portion, wherein the zeolite seed portion includes the existing zeolite seeds from the seed growth solution, wherein the zeolite seed portion has a characteristic size β, wherein the epitaxially grown fins have a characteristic size α, wherein β is greater than α, and wherein α is less than 50 nm.
2. The method of claim 1, wherein the one or more framework source precursors comprise sodium silicate, tetraethyl orthosilicate, colloidal silicate, SiO2, aluminum sulfate, aluminum hydroxide, Al2O3, or a combination thereof.
3. The method of claim 1, wherein the structure directing agent is an inorganic structure directing agent, an organic structure directing agent, or a combination thereof.
4. The method of claim 1, wherein the structure directing agent is selected from the group consisting of pyrrolidine, tetrapropylammonium hydroxide, 1,8-octanediamine, cyclohexylamine, and tetrabutylammonium hydroxide.
5. The method of claim 1, wherein the hydroxide source is Na2O or K2O. 6 . The method of claim 1 , wherein the secondary growth solution has a molar composition ratio of the first framework source precursor to the second framework source precursor of 40:1 to 120:
1.
7. The method of claim 6, wherein the first framework source precursor is SiO2, and the second framework source precursor is Al2O3. 8 . The method of claim 1 , wherein the secondary growth solution has a molar composition ratio of the framework source precursor to the structure directing agent of 2:1 to 15:
1. 9 . The method of claim 1 , wherein the secondary growth solution has a molar composition ratio of a framework source precursor to a hydroxide source of 8:1 to 65:
1.
10. The method of claim 1, wherein the fin-shaped zeolite crystals are of MEL type, MFI type, or FER type.
11. The method of claim 2, wherein the SiO2 is fumed silica.
12. Fin-shaped zeolite crystals prepared by the method of claim 1.
13. Fin-shaped zeolite crystals comprising: a zeolite seed portion, wherein the seed portion comprises a single crystallographic orientation, and wherein the seed portion comprises a pore network; and A plurality of epitaxially grown fins extending from an outer surface of the zeolite seed portion, wherein the epitaxially grown fins comprise a single crystallographic orientation that is the same as the single crystallographic orientation of the zeolite seed portion, and wherein the epitaxially grown fins comprise a pore network connected to the pore network of the zeolite seed portion.
14. The finned zeolite crystal of claim 13, wherein the zeolite seed portion has a characteristic dimension β, wherein the epitaxially grown fins have a characteristic dimension α, and wherein β is greater than α.
15. The finned zeolite crystal of claim 14, wherein α is less than 50 nm. 16 . The finned zeolite crystal of claim 14 , wherein adjacent epitaxially grown fins are separated by a spacing, and wherein an average spacing between adjacent epitaxially grown fins is 20 nm to 100 nm. 17 . The fin-shaped zeolite crystal according to claim 13 , wherein the fin-shaped zeolite crystal is of MEL type, MFI type or FER type.
